EVALUATION OF RESERVATION SYSTEM SUCCESS USING DELONE AND MCLEAN METHOD AT PT. MABRUK HOTEL - Maman Masyhuri; Nilo Legowo (International Journal of Economy, Education and Entrepreneurship, 2023)
This research intends to determine the relationship between system quality, information quality, and service quality as exogenous variables to system use and user satisfaction as an endogenous variable, then test to determine the effect of system use and user satisfaction of the net benefit variable. This research uses the Delone & McLean success model and probability sampling technique of 97 respondents from guest hotels in Mambruk who use or have used the reservation system. The method of study used to test the reservation system was SEM (Structural Equation Modeling), along with path analysis performed with lisrel 8.0. Application to describe the relationship of variables latent indicators (measurement models) and relationships between latent variables (structural models), and the results showed that the t-value of system quality (1.25), information quality (0,56), and user satisfaction (0,48) were not significant. However, service quality (3,59) is essential for the system use variable. System quality (5.07), information quality (4.22), and service quality (5.95) significantly affect the user satisfaction variable, then user satisfaction (3.61) and system use (2.06) were significant to the net benefit variable. Fit model is a good fit based on the criteria GOF (Goodness of appropriate) with the results of the chi-square 274.06, with a significance level of probability (0.0013), the degree of freedom 240, RMSEA (0.038), ECVI (48.85), AIC (394.06), CAIC (4775.85), NFI (0.93), NNFI (0.98), CFI (0.98), IFI (0.98), AGFI (0.76), PGFI 0.65). The influence value of system quality (0,22), information quality (0,16), and service quality (0,36) to system use and user satisfaction, then influence the relationship value of user satisfaction (0,62) to system use and net benefit. The achievement of reservation system success results in effectiveness and efficiency in using the reservation system